2015
DOI: 10.1021/acs.joc.5b02273
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid-Catalyzed Reactions of Trifluoroborate Salts with Benzhydryl Alcohols

Abstract: Brønsted acid-catalyzed carbon-carbon bond forming methodology using potassium alkynyl- and alkenyltrifluoroborate salts has been developed. Organotrifluoroborates react with benzhydryl alcohols to afford a broad range of alkynes and alkenes in good to excellent yields. This protocol features good atom economy because organotrifluoroborate salts and alcohols react in a 1:1 ratio. Furthermore, a variety of unprotected functional groups were tolerated under the developed conditions, including amide, aldehyde, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 75 publications
0
21
1
Order By: Relevance
“…Previously, we discovered that tetrafluoroboric acid (HBF4) is an effective catalyst for the reactions of trifluoroborate salts [4,5]. To investigate the efficiency of the HBF4 as a Brønsted acidcatalyst towards the substitution of 2-ethoxytetrahydrofuran, we first looked at using unsubstituted potassium phenylacetylenetrifluoroborate salt (S1) as a model substrate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we discovered that tetrafluoroboric acid (HBF4) is an effective catalyst for the reactions of trifluoroborate salts [4,5]. To investigate the efficiency of the HBF4 as a Brønsted acidcatalyst towards the substitution of 2-ethoxytetrahydrofuran, we first looked at using unsubstituted potassium phenylacetylenetrifluoroborate salt (S1) as a model substrate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To our delight, product 1a was obtained in an excellent 92% yield ( We found that the substitution was achieved with 75% yield of the desired product 1a when a slight excess of 1.1 equivalents of both the organotrifluoroborate (S1) and HBF 4 acid catalyst were used (Table 1, entry 1). Attempts to use an alternative acid such as trifluoroacetic acid, which has a pK a similar to that of HBF 4 , only resulted in trace amounts of product formation (Table 1, entry 2). Our previous studies indicated that increasing the amounts of trifluoroborate salt and HBF 4¨O Et 2 to 1.5 equivalents resulted in a higher yield for the alkynylation of ketals [5].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations